Revision of the Afrotropical genus Susua Lugo-Ortiz & McCafferty 1998 (Ephemeroptera: Baetidae: Protopatellata) - Kluge, Nikita J.; Gattolliat, Jean-Luc; Salles, Frederico F.; Novikova, Eugenia A. (Zootaxa, 2018)
The species originally described as Cheleocloeon sigiensis Gillies 2001 is moved to the genus Susua Lugo-Ortiz & McCafferty 1998. Additional descriptions of Susua sigiensis (Gillies 2001) are given based on male and female imagoes reared from larvae from several localities in Tanzania (including the type locality in the Upper Sigi Basin). Susua niandanensis (Wuillot in Wuillot & Gillies 1993) is redescribed based on larvae and male imagoes from Guinea, Mali, Côte d’Ivoire and Zambia. The genus Susua belongs to the plesiomorphon Protopatellata Kluge & Novikova 2011 and has an Afrotropical distribution; Susua is closely related to Crassabwa Lugo-Ortiz & McCafferty 1996. General characteristics of Susua are given based on the two known species.